Changing local recombination patterns in Arabidopsis by CRISPR/Cas mediated chromosome engineering - Schmidt, Carla (Nat Commun, 2020)
Chromosomal inversions are recurrent rearrangements that occur between different plant isolates or cultivars. Such inversions may underlie reproductive isolation in evolution and represent a major obstacle for classical breeding as no crossovers can be observed between inverted sequences on homologous chromosomes. The heterochromatic knob (hk4S) on chromosome 4 is the most well-known inversion of Arabidopsis. If a knob carrying accession such as Col-0 is crossed with a knob-less accession such as Ler-1, crossovers cannot be recovered within the inverted region. Our work shows that by egg-cell specific expression of the Cas9 nuclease from Staphylococcus aureus, a targeted reversal of the 1.1 Mb long hk4S-inversion can be achieved. By crossing Col-0 harbouring the rearranged chromosome 4 with Ler-1, meiotic crossovers can be restored into a region with previously no detectable genetic exchange. The strategy of somatic chromosome engineering for breaking genetic linkage has huge potential for application in plant breeding.